2012
DOI: 10.1097/cmr.0b013e328357d796
|View full text |Cite
|
Sign up to set email alerts
|

Variability in melanoma post-treatment surveillance practices by country and physician specialty

Abstract: Background There are no evidence-based guidelines for surveillance of patients with melanoma following surgical treatment. We performed a systematic review to identify current stage-specific surveillance practices for patients with melanoma by country and physician specialty. Methods Three major medical indices, MEDLINE, the Cochrane Library database, and Scopus, were reviewed to identify articles published in January 1970 to October 2011 that included detailed information about surveillance of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 92 publications
0
65
0
3
Order By: Relevance
“…Approximately 1–8% of melanoma survivors will develop a second primary melanoma in their lifetime, which is often thinner than the first primary (25). Physicians, more often than patients, detect the second primary melanoma.…”
Section: Melanoma Surveillancementioning
confidence: 99%
See 3 more Smart Citations
“…Approximately 1–8% of melanoma survivors will develop a second primary melanoma in their lifetime, which is often thinner than the first primary (25). Physicians, more often than patients, detect the second primary melanoma.…”
Section: Melanoma Surveillancementioning
confidence: 99%
“…Cromwell et al . (25) recently performed a systemic review of published surveillance strategies from 1970 to 2011; they found significant variation in follow-up relative to disease state, country of origin, and physician specialty. Greatest variation in surveillance frequency was noted in stage I patients, which ranged from 1–6 visits/year for the first 2 years of treatment, and with regard to the use of routine diagnostic imaging and laboratory evaluations.…”
Section: Melanoma Surveillancementioning
confidence: 99%
See 2 more Smart Citations
“…17 There is evidence that~30% of melanoma patients report clinically relevant psychological distress. 18 Although there is some evidence that early detection of recurrence can improve patient survival 15,19,20 and the benefit of detecting early a new primary melanoma is generally accepted, 21 evidence is inconclusive whether intensive surveillance can meaningfully contribute to early detection; 2 75% of patients detect their own recurrence outside of scheduled follow-up visits. 2,9 Evidence first needs to be generated on current follow-up practices to identify models of care (e.g.…”
Section: Activities May Includementioning
confidence: 99%